Implementasi dan Evaluasi Sistem Keyword Spotting Real-Time berbasis Google Speech API pada Asisten Cerdas Sederhana di Google Colaboratory - Singgih Astaguna T; Muhammad Fauzan Yusuf; Izza Etthiyyah RN; Dessy Ana Laila Sari (PT. Global Research Collaboration, 2025)
The development of voice recognition technology, particularly Keyword Spotting (KWS) , offers significant potential for critical applications such as emergency response systems in the healthcare sector. The use of cloud-based Application Programming Interfaces (APIs) like the Google Speech API provides an accessible development pathway for these applications , but its performance in specific contexts, such as for the Indonesian language, requires thorough evaluation. This study aims to implement and evaluate the performance of a real-time KWS system based on the Google Speech API within a simple smart assistant prototype designed for healthcare emergency scenarios. The system was implemented on Google Colaboratory using a Text-based KWS approach. Quantitative testing was conducted with two male participants who uttered five Indonesian target keywords (